The Validity of Cryptocurrency Transactions and the Analysis of Associated Disputes - Hossein Qahari; Javad Hosseinzadeh (حقوق فناوریهای نوین)
Cryptocurrency is one of the modern tools that aims to replace money and is sometimes traded among citizens as a commodity or a means of debt payment. Even though the legislator has banned cryptocurrency exchange in domestic transactions, its buying and selling is common among some people. Therefore, it's necessary first to find the situation of such transactions and then the type of reaction of the court to the lawsuit on cryptocurrency among the provisions and in the shadow of general legal principles. This article seeks to answer these questions: 1) What is the legal status of cryptocurrency trading? 2) In a legal dispute of cryptocurrency transaction, can the promise request the court to hand over the cryptocurrency by the promisor? 3) Can a right not protected by the law be claimed in court? The authors believe that cryptocurrency transactions can be done in two ways: first, in the form of a “trade item" and second, as a “means of payment. "The cryptocurrency transaction is void under the law, but if it is agreed upon as a means of payment, the contract is valid. But we cannot use cryptocurrency as the price of the transaction, and fiat money should be given instead. 1. Introduction The complex economic relations in the current era increasingly demand the provision of efficient, rational, and comprehensive legal norms. Non-compliance with the law and exploitative behaviors, which reflect a clear image of the present culture, pose a threat to the economic and social health of our nation. Among the causes of such risky behavior, factors such as concerns over the continuous depreciation of the national currency and widespread changes in people’s welfare standards can be highlighted. However, irrespective of the reasons behind this dominant profit-seeking behavior, ignoring government regulations—if not properly identified and controlled—can have devastating consequences across political, economic, social, and cultural domains. One area of evasion from the law is the buying and selling of cryptocurrencies or the commitment to settle debts through the delivery of cryptocurrencies, without regard to their official prohibition. With the emergence of cryptocurrencies, transactions based on these tools have gained significant popularity among citizens in various countries. Individuals use their electronic wallets to buy and sell a growing range of cryptocurrencies, and in some cases, they also utilize them as a means of payment. The approach of different governments toward these types of transactions is not uniform. In Iran, the legislator has prohibited the buying and selling of cryptocurrencies, while allowing their mining. However, miners are obligated to sell the mined cryptocurrency to a government-approved exchange. Despite this, government regulations have been somewhat disregarded, and it can be said that, despite the explicit legal prohibition, cryptocurrency transactions have become commonplace among the public.